Device effects: Results from choice experiments in an agritourism context - Héctor Tavárez; Mildred Cortés (Economía Agraria y Recursos Naturales)
This study uses a questionnaire to examine device use effects in choice experiments and to estimate willingness to pay (WTP) values for agritourism-related activities. The results indicate that respondents using devices with large screens are more confident of their responses, dedicate more time to the valuation exercise, and select the status quo option less frequently. However, WTP for agritourism and perceived choice experiment complexity are invariant with regards to the device. Respondents’ WTP for selected agritourism activities varies from $5 to $21 per visit.